Disaster management in Bangladesh: developing an effective emergency supply chain network - Yogesh Dwivedi (Annals of Operations Research, 2019)
Bangladesh is a disaster prone country and faces the challenges of managing naturaldisasters every year, particularly from floods and cyclones. To face those calamities,the emergency supply chain management of Bangladesh is traditionally engaged inmanaging the entire network and are the key stakeholders for storing relief items,estimating damage and people affected, distributing reliefs and other necessarysupporting services, and fulfilling the requirements of distressed people during andafter any disaster. However, like any humanitarian supply chain system, thisemergency supply chain has scope for improvement, to minimize the weaknesses andproblems and to establish an effective supply chain system. In this context, a thoroughfield investigation in several districts was conducted among the employees of theinteroperable organizations. Information was collected from the employees of all theparticipating organizations involved in disaster management through a semi-structuredquestionnaire based survey. Based on this comprehensive study, several major andminor strengths, opportunities, threats and weaknesses of the existing emergencysupply chain have been established. Considering those problems under differentdrivers of the supply chain, specific categorizations of problems are identified.Reflecting those issues, an emergency supply chain for disaster management isproposed in this study.